Analisis Kelayakan Usaha Ternak Kambing Gibas Di Desa Nglumber Kecamatan Kepohbaru Kabupaten Bojonegoro - Anis Mahmudatul Janah; I Made Suparta (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to analyze the income, profits and feasibility of the gibas goat farming business in Nglumber Village, Kepohbaru District, Bojonegoro Regency. This research used as informants 6 gibas goat entrepreneurs in Nglumber Village, Kepohbaru District, Bojonegoro Regency. The analytical tools used in this research are total production costs, revenues, profits and business feasibility. The results obtained from this research are that the average total production costs incurred are IDR 112,362,000 month, the average revenue obtained is IDR 79,916,667/month, and the average profit obtained is IDR 9,430,461/month. The results of calculating 3 (three) feasibility parameters for 6 gibas goat livestock entrepreneurs in Nglumber Village, Kepohbaru District, Bojonegoro Regency, can be seen that the R/C ratio obtained an average value of 1.3 > 1, the B/C ratio obtained an average value equal to 0.13 > 0, and ROI obtained an average value of 7%. Therefore, the gibas goat farming business in Nglumber Village, Kepohbaru District, Bojonegoro Regency is feasible.